SOCIO-PSYCHOLOGICAL FEATURES OF RUSSIAN-BELARUSIAN BORDER AREAS - Anton Sergeevich Kuzavko (Science and Innovation Center Publishing House, 2020)
Purpose. Identification of the specifics of the socio-psychological motives of residents that determine the opportunities and main threats in the formation of a business unit in the border region.